Correlation of Quadriceps and Hamstring Muscles Strength with Knee Osteoarthritis Stages and Pain Levels in Elderly Female Subjects - Mohammad Fathul Qorib 1, Hening Laswati1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Osteoarthritis (OA) is one of the most common disease occur in elderly. It is commonly occurs in knee, hips and interphalangeal joints Pain caused by knee OA may result in functional disorders that affect patient’s life quality. Objective: To analyze correlation of quadriceps and hamstring muscles strength with knee OA stages and pain levels in elderly female subjects. Methods: 38 elderly female subjects (average age of 67.18 ± 4.91) were assessed for pain scale using numeric rating scale (NRS). We used 1RM protocol (EN-Tree) to measure quadriceps and hamstring muscles strength. We performed anterior-posterior and lateral knee X-rays to determine OA stage. The process of data analysis was conducted using several tests, including Kolmogorov-Smirnov test, Pearson’s correlation test, Spearman’s correlation test and Mann-Whitney test to measure difference between knee OA level using 1RM quadriceps muscle and quadriceps/hamstring (Q/H) ratio. Results: The average NRS was 3.68 ± 1.19, 1RM quadriceps and hamstring muscles strength were 2.68 ± 1.23 and 1.11 ± 0.44, respectively, quadricep/hamstring ratio (Q/H) was 2.53 ± 0.95. A total of 30 subjects had OA stage 2, while 8 subjects had OA stage 3. Conclusion: The 1RM quadriceps and hamstring muscles was not correlated with NRS. There was no difference in 1RM quadriceps and hamstring muscles between subjects with OA stage 2 and 3. We found a positive correlation between Q/H ratio and the NRS. The Q/H ratio in subjects with OA level 2and 3 was different.